2003
DOI: 10.1099/mic.0.26541-0
|View full text |Cite
|
Sign up to set email alerts
|

Attachment to and biofilm formation on abiotic surfaces by Acinetobacter baumannii: involvement of a novel chaperone-usher pili assembly system

Abstract: Acinetobacter baumannii causes severe infections in compromised patients, survives on abiotic surfaces in hospital environments and colonizes different medical devices. In this study the analysis of the processes involved in surface attachment and biofilm formation by the prototype strain 19606 was initiated. This strain attaches to and forms biofilm structures on plastic and glass surfaces, particularly at the liquid-air interface of cultures incubated stagnantly. The cell aggregates, which contain cell stack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
531
1
10

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 519 publications
(580 citation statements)
references
References 40 publications
22
531
1
10
Order By: Relevance
“…One of the earliest studies showed the importance of exopolysaccharide production and pilus formation to biofilm development in A. baumannii (5). Using random mutagenesis and screening of mutants for biofilm formation, csuE was identified as being important in bacterial attachment and biofilm formation, as well as pili production and assembly (5). Further genetic characterization identified a csu operon, made up of six genes (csuA/BABCDE), which encodes a chaperoneusher secretion system that is important for pilus assembly (5).…”
Section: Biofilm Formation and Use Of In Vitro Abiotic Models To Studmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the earliest studies showed the importance of exopolysaccharide production and pilus formation to biofilm development in A. baumannii (5). Using random mutagenesis and screening of mutants for biofilm formation, csuE was identified as being important in bacterial attachment and biofilm formation, as well as pili production and assembly (5). Further genetic characterization identified a csu operon, made up of six genes (csuA/BABCDE), which encodes a chaperoneusher secretion system that is important for pilus assembly (5).…”
Section: Biofilm Formation and Use Of In Vitro Abiotic Models To Studmentioning
confidence: 99%
“…For example, the mean survival time of clinical isolates on glass coverslips when subjected to dehydrating conditions was 27 days (26), and it has been shown that A. baumannii can survive on hospital bed rails for up to 9 days (27). Indeed, the pioneering studies on A. baumannii pathogenesis focused on the ability of A. baumannii to form biofilms on abiotic surfaces, as well as the organism's ability to survive in iron-limiting conditions (5,11,12). The biofilm studies were mainly performed using a 96-well polystyrene assay, as well as attachment to glass and other plastic surfaces.…”
Section: Biofilm Formation and Use Of In Vitro Abiotic Models To Studmentioning
confidence: 99%
See 2 more Smart Citations
“…V. parahaemolyticus encodes a homologue of type I pili that is most similar to the CsuA/B operon from Acinetobacter baumannii (7) and homologues of two wellstudied type IV pili from vibrios, the mannose-sensitive hemagglutinin (MSHA) and the chitin-regulated pilus (PilA) (http://img .jgi.doe.gov/) (8,9). Vibrio vulnificus uses PilA for persistence in Crassostrea virginica (10,11).…”
mentioning
confidence: 99%